1999
DOI: 10.1097/00005650-199905001-00003
|View full text |Cite
|
Sign up to set email alerts
|

The SF-36 Health Survey as a Generic Outcome Measure in Clinical Trials of Patients With Osteoarthritis and Rheumatoid Arthritis

Abstract: Results of this study support the validity of the SF-36 to document the health burden of arthritis and as a measure of generic health outcome for clinical trials of alternative treatments for osteoarthritis and rheumatoid arthritis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
130
1
4

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(139 citation statements)
references
References 28 publications
4
130
1
4
Order By: Relevance
“…As in our study, other studies have also found associations between capability variables (6-minute gait distance, index of ambulatory independence, SF-36 scores, WOMAC scores, gait speed, stride length, stair ascent duration), on the one hand, and measures of locomotor ability, on the other hand, in persons with OA (44,53,110,165), TKA (133), and in elderly people (42,139,145,146,159). All these capability variables, except stride length, have previously been used in regression models predicting locomotor ability (133,139,143) and self-perceived functional ability (6,20,103,145,146) in various populations.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As in our study, other studies have also found associations between capability variables (6-minute gait distance, index of ambulatory independence, SF-36 scores, WOMAC scores, gait speed, stride length, stair ascent duration), on the one hand, and measures of locomotor ability, on the other hand, in persons with OA (44,53,110,165), TKA (133), and in elderly people (42,139,145,146,159). All these capability variables, except stride length, have previously been used in regression models predicting locomotor ability (133,139,143) and self-perceived functional ability (6,20,103,145,146) in various populations.…”
Section: Discussionsupporting
confidence: 88%
“…The resulting score can vary from 0 to 123, with higher scores indicating the most favorable state of health. The SF-36 has good metrologic properties (107,110,111,114,115,(117)(118)(119)(120)(121)(122)(123)(124)(125).…”
Section: Ambulatory Independence (Independ)mentioning
confidence: 99%
“…The effect of etanercept on psoriasis was measured as improvement in target lesions, in the dermatologist's static global assessment of psoriasis, and in the Psoriasis Area and Severity Index (PASI 50 and PASI 75) (20). Other analyses of outcome included quality of life, as measured by the Short Form 36 (SF-36) Health Survey (21), and function, as evaluated using the Health Assessment Questionnaire (HAQ) (22).…”
Section: Methodsmentioning
confidence: 99%
“…The HOOS is a valid, reliable, and responsive self-administered instrument with ICC values ranging from 0.78 to 0.91 depending on the subscale [24]. The SF-36 is a reliable self-report survey (ICC = 0.75-0.91) [25] for assessing health-related quality of life [5,7,55]. All participants reported their physical activity level using the UCLA Activity Scale [57].…”
Section: Strength Testing Proceduresmentioning
confidence: 99%